Reduced Self-Aggregation and Improved Stability of Silica-Coated Fe3O4/Ag SERS-Active Nanotags Functionalized With 2-Mercaptoethanesulfonate - Żygieło, Maria; Piotrowski, Piotr; Witkowski, Marcin; Cichowicz, Grzegorz; Szczytko, Jacek; Królikowska, Agata (Frontiers in Chemistry, 2021)
Nanocomposites combining magnetic and plasmonic properties are very attractive within the field of surface-enhanced Raman scattering (SERS) spectroscopy. Applications presented so far take advantage of not only the cooperation of both components but also synergy (enhanced properties), leading to multi-approach analysis. While many methods were proposed to synthesize such plasmonic-magnetic nanoparticles, the issue of their collective magnetic behavior, inducing irreversible self-aggregation, has not been addressed yet. Thus, here we present a simple and fast method to overcome this problem, employing 2-mercaptoethanesulfonate (MES) ions as both a SERS tag and primer molecules in the silanization process of the previously fabricated Fe3O4/Ag nanocomposite. The use of MES favored the formation of silica-coated nanomaterial comprised of well-dispersed small clusters of Fe3O4/Ag nanoparticles. Furthermore, adsorbed MES molecules provided a reliable SERS response, which was successfully detected after magnetic assembly of the Fe3O4/Ag@MES@SiO2 on the surface of the banknote. Improved chemical stability after coating with a silica layer was also found when the nanocomposite was exposed to suspension of yeast cells. This work may be considered the first report on the application of 2-mercaptoethanesulfonate not only providing a photostable SERS signal due to a non-aromatic Raman reporter but also acting as a silanization primer and a factor responsible for a substantial reduction of the self-aggregation of the plasmonic-magnetic nanocomposite. Additionally, here obtained Fe3O4/Ag@MES@SiO2 SERS nanotags showed the potential as security labels for the authentication purposes, retaining its original SERS performance after deposition on the banknote.